Student reasoning constrained by the didactical contract - Måsøval, Heidi S. (NOMAD Nordic Studies in Mathematics Education, 2005)
This paper presents an analysis of an observation of student teachers’ small-group work on a generalization problem in algebra. I begin my analysis by looking at the student teachers’ attention to the teacher educator’s thinking, at the cost of their own interpretation of the problem. Further analysis deals with the difficulties in changing representation from natural language to mathematical symbols. The analysis is based on Brousseau’s theory of didactical situations in mathematics, and a semiotic approach to the problem of algebraic reference, informed by Radford.